Necrotizing Fasciitis: Diagnostic Challenges in a Mute Bedridden Patient with Atypical Laboratory Parameters - Ghan-Shyam Lohiya; Lilia Tan-Figueroa; Vijay Krishna; Sunita Lohiya (Case Reports in Medicine)
A 27-year-old mute bedridden patient required parenteral corticosteroids and antibiotics, and hospitalization for an acute respiratory illness. After 2 days, staff noted a ~0.3 cm blister on the patient’s right heel. Within 19 hours, blistering increased and the foot became partly gangrenous. The patient developed high fever (40.3°C), and leukocytosis (count: 13×109/L; was 6.5×109/L ten days earlier). Necrotizing fasciitis (NF) was diagnosed and treated with emergency leg amputation. Histopathology revealed necrosis of fascia, muscle, subcutaneous tissue, and skin. In bedridden patients, corticosteroids may particularly facilitate serious infections, and initial NF blistering may be mistaken for pressure ulcers. Vigilant and frequent whole body monitoring is necessary for all patients incapable of verbalizing their symptoms.